THE COUNT OF MONTE CRISTO - Dumas, Alexandre, 1802-1870, author 199563; Vogel, Marvina G., editor 640072 (Oxford : Oxford University Press, 1998)
Revenge At All Cost! A young sailor returns home from a dangerous voyage. His father and his sweetheart are waiting for him. But an act of jealous treachery changes his life forever! An unexpected meeting changes everything and the man who was once an unknown sailor emerges as THE COUNT OF MONTE CRISTO, mysterious, rich, and powerful enough to take the ultimate revenge against his enemies.